Design and Potential of a Hybrid Biogas Reactor with Solar Panels for Energy Conversion in Tropical Areas - Nukhe Andri Silviana; Parluhutan Panjaitan; Ninny A Siregar; Nuril Mahda; Rana Fathinah Ananda; Yuana Delvika; Yudi Daeng Polewangi; Habib Satria; Indri Dayana (Journal of Applied Engineering and Technological Science (JAETS), 2026)
Improperly managed cow dung can pollute the environment, causing unpleasant odors and contaminating groundwater. Therefore, a portable biogas reactor with a floating digester model was designed to process the waste into biogas energy and organic fertilizer while reducing the impact of pollution. The design method used the Pahl and Beitz approach, starting from task clarification to design development, focusing on portability, efficiency, and ease of operation. The reactor was designed to be able to process up to 300 kg of waste per month and was equipped with solar panels as an alternative energy source to operate the heating agitator and sensors, making it suitable for use in areas with minimal electricity access. The system was tested based on the daily performance of photovoltaic PV from 7:00 am to 6:00 pm. Based on the results of observations, a typical pattern of the PV system with the highest performance occurred when the light intensity was maximum at 12:00 pm. This hybrid system and reactor has the potential to be a sustainable solution in livestock waste management and support environmentally friendly agricultural practices.